La Cooperación Sur – Sur: ¿nuevas formas de actuar y/o nuevas representaciones de poder?. La cooperación brasileña, periodo 2008 - 2012 - Lombardo Torres, Paul (2014)
In recent years, South-South Cooperation (SSC) has developed a growing participation in the global realm. This is due to the political, economic and social changes that are taking place in the current world order; changes affecting both structure and agency. This new type of cooperation maintains a departure from traditional cooperation and does not seek to erase the efforts of the North but rather seeks new power relations. Likewise, Brazil forms a part of the changes in the world order. Today Brazil has become an active player in the global scope as well as the regional scope; its presence in the global scope has increased to the point that is part of powerful groups such as the BRICS, IBSA and the G20; while in the regional scope it was the drive of the Union of South American Nations (UNASUR). The aim of this study is to analyze whether the International Cooperation of Brazil in South America reflects a departure from traditional cooperation and/or responds to specific interests, and the period of study is 2008 - 2012. Through the main perspectives of the International Political Economy, the possible focuses will be discussed in regards to the topics of Power-Development, as the form of acting within the world order; Cooperation, as a strategic instrument of the country’s foreign policy; and Regionalism, as a characteristic of the dynamics of globalization in today’s world.